Dealing with disagreement: The roles of topic familiarity and disagreement explanation in evaluation of conflicting expert claims and sources. (October 2020) - Barzilai, Sarit; Thomm, Eva; Shlomi-Elooz, Talia
Abstract: Learners may increasingly encounter conflicting expert reports. However, little is known about how they deal with this challenge. We examined how learners' familiarity with a controversial historical topic affects their epistemic judgments of conflicting expert claims and sources, the interplay of their claim and source evaluation strategies, and their meta-epistemic understanding of the legitimacy of the disagreement (absolutist, multiplist, and evaluativist perspectives). In two studies, topic familiarity increased agreement with belief-consistent expert claims and the perceived trustworthiness of the expert who presented these claims. Topic familiarity also impacted the coordination of evaluation strategies and led to greater reliance on knowledge-based validation. However, topic familiarity did not affect meta-epistemic understanding of the legitimacy of the controversy. In the second study, reading an explanation about reasons for disagreements between historians resulted in higher evaluativism. Teaching about expert disagreement may be a productive approach for promoting appreciation of the diversity of knowledge. Highlights: We examined how learners evaluate conflicting expert reports. Topic familiarity led to greater reliance on topic knowledge to evaluate claims and sources. Topic knowledge and beliefs impacted claim agreement and source trustworthiness judgements. Topic familiarity did not affect meta-epistemic understanding of the disagreement. Reading a disagreement explanation increased evaluativist understanding of the disagreement.